2013
DOI: 10.1039/c3cp52697f
|View full text |Cite
|
Sign up to set email alerts
|

Improved cathode for high efficient microbial-catalyzed reduction in microbial electrosynthesis cells

Abstract: Microbial electrosynthesis cells (MECs) are devices wherein microorganisms can electrochemically interact with electrodes, directly donating or accepting electrons from electrode surfaces. Here, we developed a novel cathode by using nickel nanowires anchored to graphite for the improvement of microbial-catalyzed reduction in MEC cathode chamber. This porous nickel-nanowire-network-coated graphite electrode increased the interfacial area and interfacial interactions between the cathode surface and the microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(82 citation statements)
references
References 41 publications
3
79
0
Order By: Relevance
“…Graphite displays a strong microwave absorption ability and may yield "hot spots". 50,51 Microwave treatment and temperature change in water are related (Table S1). The combination of a hot HOPG substrate and temperature change in water by microwave irradiation may be responsible for the formation of interfacial nanobubbles.…”
Section: Discussionmentioning
confidence: 99%
“…Graphite displays a strong microwave absorption ability and may yield "hot spots". 50,51 Microwave treatment and temperature change in water are related (Table S1). The combination of a hot HOPG substrate and temperature change in water by microwave irradiation may be responsible for the formation of interfacial nanobubbles.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, introduction of positive charged functional groups at carbon cloth electrodes significantly improves formation and performance of Sporomusa ovate films used for electrosynthetic production of acetate in a microbial electrolysis cell [96][97] . Carbon nanotube (CNT) modified electrodes prove superior to planar electrodes for mixed consortia biofilm formation and acetate production rates 75 .…”
Section: Surface Chemistry In Microbial Bes Designmentioning
confidence: 99%
“…To the best of our knowledge, only Lovley et al (2013) [10,11] have very recently proposed a number of modified electrode materials for the improvement of cathodic processes.…”
Section: Biocathode Electrode Materials For Mesmentioning
confidence: 99%
“…MES remains a nascent concept with only few studies that have demonstrated the process in laboratory scale using either pure cultures [8][9][10][11] or mixed microbial consortia [12][13][14][15][16][17][18][19]73].…”
Section: Microbial Electrosynthesis From Co2 To Organics-a Reviewmentioning
confidence: 99%
See 1 more Smart Citation